The unsung gay heroes of American education: the lived experiences of the gay and lesbian educator - Syng, Roger Andre (Kansas State University, 2018)
Much of the research on gays and lesbians in education has focused on their experiences as a marginalized group. There has been much progress in the understanding of gays and lesbians as a whole and the research shows that indeed this group has shown great contributions to the field. However, a close examination of the history of gays and lesbians also presents considerable evidence that the civil rights of gays and lesbians can indeed influence their professional lives regardless of occupation. This qualitative multiple case study examined the life experiences of the gay or lesbian educator in light of civil rights legislation that continues to influence our lives. Tenured educators were interviewed regarding their lived experiences early in life, during their education and growth in the profession, and currently as educators. The research used reputational snow ball sampling to discover these educators. The concepts behind Queer Theory and Queer Legal Theory were used in examining data in the context of civil rights involving gay and lesbian teachers. This study adds to the body of literature regarding sensitivity and tolerance for gays and lesbians as well as materials designed to enlighten teacher training in sensitivity, and awareness of gay, and lesbian teachers and administrators.
Keywords: Gay; Lesbian; Educator; Queer; Heroes; American